In what ways are adolescents who engage in self-harm or experience thoughts of self-harm different in terms of help-seeking, communication and coping strategies? - Evans, E; Hawton, K; Rodham, K (2005)
The purpose of this study was to ascertain whether adolescents who deliberately harmed themselves or had thoughts of self-harm differed from other adolescents in terms of help-seeking, communication and coping strategies. The participants were 6020 15-16 year-old school pupils who were surveyed using an anonymous self-report questionnaire. Adolescents with one or more episodes of deliberate self-harm (DSH) in the previous year were more likely to identify themselves as having serious problems than other adolescents. However, a substantial proportion of adolescents with either DSH or thoughts of self-harm did not identify themselves as having serious problems. Adolescents with DSH were most likely to feel the need for help but not try to get any; they were less able to talk to family members and teachers and had fewer categories of people who they were able to talk to. Like other adolescents, those with DSH or thoughts of self-harm were more likely to seek and receive help from their friends than from other sources. They differed from other adolescents in terms of coping strategies they reported employing when faced with difficulties, showing less focus on problems and more avoidant behaviours. The findings have important implications for preventive strategies, including educational programmes on emotional health and coping, and for the clinical care of adolescents identified as at risk or having self-harmed.